HISTORY OF BAR FORMATION AND DEVELOPMENT IN USSR (1917-1991) - Gerasimova, Elena; Shestak, Viktor; Sangadzhiev, Badma; Kondratuk, Diana; Goncharov, Petr (Revista Notas Históricas y Geográficas, 2021)
The purpose of the article is to study the historical stages in the establishment and development of the Bar in the Soviet Union. Eight historical periods of judicial administration development were substantiated that allow one to trace the problems during the formation and institutional development of the institution of the Bar that has been associated with the organizational court management up to the 1990s, as well as the evolution of the institution of the Bar. The leading method consists in studying the historiographic periodization of the Bar development and is determined by milestones in the formation and development of the judiciary as a whole and changes in the legislation that regulates the judicial system and judicial proceedings. The enhancement of legitimacy is the most important function of the state that creates the corresponding structures and law enforcement bodies.